2021
DOI: 10.1002/eap.2258
|View full text |Cite
|
Sign up to set email alerts
|

Partial and complete dependency among data sets has minimal consequence on estimates from integrated population models

Abstract: Integrated population models (IPMs) are widely used to combine disparate data sets in joint analysis to better understand population dynamics and provide guidance for conservation activities. An often-cited assumption of IPMs is independence among component data sets within the combined likelihood. Dependency among data sets should lead to underestimation of variance and bias because individuals contribute data to more than one data set. In practice, studied individuals often occur in multiple data sets in IPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
2
19
1
Order By: Relevance
“…This assumption is violated in our case; the adult survival analysis shares carcass data with the recovery analysis and mark-recapture data with the reproductive analysis. Two simulation studies 17,46 found that violating this assumption had little effect, but as their analyses were not identical to ours, this assumption violation still might diminish the accuracy of our estimates. Simulations by Rieke et al 47 show that assumption violations in one of the model components can dramatically reduce the accuracy of estimates of latent parameters.…”
Section: Discussioncontrasting
confidence: 52%
“…This assumption is violated in our case; the adult survival analysis shares carcass data with the recovery analysis and mark-recapture data with the reproductive analysis. Two simulation studies 17,46 found that violating this assumption had little effect, but as their analyses were not identical to ours, this assumption violation still might diminish the accuracy of our estimates. Simulations by Rieke et al 47 show that assumption violations in one of the model components can dramatically reduce the accuracy of estimates of latent parameters.…”
Section: Discussioncontrasting
confidence: 52%
“…Early integrated analyses suggested that one crucial assumption of integrated models is that the datasets to be integrated are independent (Besbeas et al, 2002; Schaub & Abadi, 2011); violation of that assumption is thought to result in overestimates of precision (Lebreton et al, 1992). However, Weegman et al (2020) found no effects on parameter bias or precision from integrated population models fit to simulated data with complete overlap.…”
Section: Discussionmentioning
confidence: 81%
“…We treated our datasets as independent, but individuals may be included in more than one (and possibly all three) data types. Other studies have demonstrated minimal impacts on the accuracy of parameter estimates from IPMs using partially and completely dependent datasets (Abadi et al, 2010;Weegman et al, 2021).…”
Section: Estimation Of Model Parametersmentioning
confidence: 98%